Феномен творчої особистості редактора у контексті духовного розвитку фахівця - Бережко-Камінська, Юлія М.; Berezhko-Kaminska, Yu. M. (Волинський національний університет імені Лесі Українки, 2012)
Розглянуто поняття творчої особистості редактора, його ролі у діяльності видавництва, описано зв’язки між творчістю, особистісним зростом і професійністю в контексті духовного розвитку, окреслено два основних напрямки розвитку особистості, виділено основні фактори, поєднання яких відрізняє творчу особистість редактора поміж інших редакторів. Creative Personality of an Editor as a Concept is analyzed. Editor’s Part in Publishing and Editing Activities as well as Interrelationship between Creative Activities, Personal Growth and Professional Level are Discussed in the Context of Spiritual Development. Two main directions of Personality Development are Two Basic Factors are Singled out which in their Combination Differentiate Editor’s Creative Personality among Other Editors.
Creative Personality of an Editor as a Phenomenon in the Context of Professional and Spiritual Evolution
Keywords: редактор; editor; особистість; personality; творча особистість редактора; editor’s creative personality; творчість редактора; editor’s creativity; духовний розвиток; spiritual evolution